A new species of Sphenomorphus (Squamata: Scincidae) from Phu Quoc Island, Vietnam with a discussion of biogeography and character state evolution in the S. stellatus group - Grismer, L. Lee; Nazarov, Roman A.; Bobrov, Vladimir V.; Poyarkov, Nikolay A. (Zootaxa, 2020)
An integrative taxonomic analysis of the Sphenomorphus stellatus group recovered a newly discovered museum specimen from Phu Quoc Island, Kien Giang Province, Vietnam as a new species most closely related to S. preylangensis from Phnom Chi in central Cambodia, approximately 175 km to the northeast. Most notably, S. phuquocensis sp. nov. lacks the derived condition of having black dorsal stripes that diagnose S. annamiticus—the sister species to S. preylangensis plus S. phuquocensis sp. nov. A BioGeoBEARS analysis recovered the ancestor of the S. stellatus group to likely have ranged across forested regions on an exposed Sunda Shelf from southwestern Indochina to Peninsular Malaysia prior to diverging into northern and southern lineages separated by the Gulf of Thailand. Episodic fluctuations in sea levels and concomitant changes in the physiography of the Mekong Delta contributed to the fragmented distribution within and between species of the northern lineage. Sphenomorphus phuquocensis sp. nov. represents the second species of reptile endemic to Phu Quoc Island.